Organic Bioelectronics: Using Highly Conjugated Polymers to Interface with Biomolecules, Cells, and Tissues in the Human Body. Issue 11 (11th October 2020) - Higgins, Stuart G.; Lo Fiego, Alessandra; Patrick, Ijeoma; Creamer, Adam; Stevens, Molly M.
Abstract: Conjugated polymers exhibit interesting material and optoelectronic properties that make them well‐suited to the development of biointerfaces. Their biologically relevant mechanical characteristics, ability to be chemically modified, and mixed electronic and ionic charge transport are captured within the diverse field of organic bioelectronics. Conjugated polymers are used in a wide range of device architectures, and cell and tissue scaffolds. These devices enable biosensing of many biomolecules, such as metabolites, nucleic acids, and more. Devices can be used to both stimulate and sense the behavior of cells and tissues. Similarly, tissue interfaces permit interaction with complex organs, aiding both fundamental biological understanding and providing new opportunities for stimulating regenerative behaviors and bioelectronic based therapeutics. Applications of these materials are broad, and much continues to be uncovered about their fundamental properties. This report covers the current understanding of the fundamentals of conjugated polymer biointerfaces and their interactions with biomolecules, cells, and tissues in the human body. An overview of current materials and devices is presented, along with highlighted major in vivo and in vitro applications. Finally, open research questions and opportunities are discussed. Abstract : Conjugated polymers are used in a wide range of organic bioelectronic interfaces both in vitro and in vivo. This report summarizes the key fundamental principles, materials, and devices. It presents recent developments in the field, with a focus on materials and devices developed for interfacing with different biomolecules, cells, and tissues of the human body.